Penerapan Peta Kendali Individuals–Moving Range (I-MR) dan Diagram Ishikawa dalam Analisis Pengendalian Kualitas Temperatur - Wulan Fransiska Lubis; Nursani Salsabillah Akza; Elisabeth Putri Dayanti (Codeverse: Journal of Emerging Digital Realities, 2026)
This study aims to analyze the stability of the temperature process using the Individuals–Moving Range (I-MR) control chart as one of the statistical quality control tools. The data used are secondary data consisting of 100 temperature observations arranged in chronological order and fulfilling the characteristics of continuous data with a single subgroup size (subgroup size = 1). The analytical method employed includes the Individuals Chart (I Chart) to monitor individual observation values and the Moving Range Chart (MR Chart) to monitor the variation between two consecutive observations. The results of the analysis indicate that, in the I Chart, all observation points are within the control limits, suggesting that the temperature process is generally in a statistically controlled condition. Meanwhile, in the MR Chart, one point was found to be outside the upper control limit, indicating the presence of a special cause variation in the form of a sudden change in temperature between two consecutive observations. To identify the possible causes of this deviation, an analysis using the Ishikawa diagram (5M+1E) was conducted, which shows that factors related to man, machine, method, material, measurement, and environment potentially affect process variation. Based on the findings, the temperature process is generally stable; however, further investigation of the deviation point is still required in order to improve process quality